(untitled) (Prithvi Journal of Research and Innovation, 2023)
The study explores the effect of parental migration on the psycho-social well-being of left-behind girls in Nepal, considering the concerns arising from the parental absence. It aims to compare the psychosocial well-being of left-behind girls with that of non-left-behind girls, taking into account factors like the duration of parental abroad stay and the level of parental concern. Conducted during the academic session of 2079 BS in Kaski District, Nepal, the study employs a cross-sectional survey design with a representative sample of 144 secondary-level students. The well-being measurement framework is adopted to gauge the participants’ overall well-being. The research delves into various aspects such as background characteristics, emotional turbulence, life contentment, and supportive mechanisms. Despite differences in age distributions and caste dynamics, both groups exhibit similar levels of life contentment and positive peer relationships. The findings of the study reveal that left-behind girls have the experience of higher emotional turbulence in some aspects, such as loneliness and unhappiness, while non-left-behind girls report more worry and sleep problems. The findings suggest that while the left-behind status is significant, other factors such as family support and personal attributes contribute to the psycho-social well-being of both left-behind girls and non-left-behind girls.